Parametric modulation of neural activity during face emotion processing in unaffected youth at familial risk for bipolar disorder - Brotman, Melissa A; Deveney, Christen M; Thomas, Laura A; Hinton, Kendra E; Yi, Jennifer Y; Pine, Daniel S; Leibenluft, Ellen (Bipolar disorders, 2014)
Objectives Both patients with pediatric bipolar disorder (BD) and unaffected youth at familial risk (AR) for the illness show impairments in face emotion labeling. Few studies, however, have examined brain regions engaged in AR youth when processing emotional faces. Moreover, studies have yet to explore neural responsiveness to subtle changes in face emotion in AR youth. Methods Sixty‐four unrelated youth, including 20 patients with BD, 15 unaffected AR youth, and 29 healthy comparisons (HC), completed functional magnetic resonance imaging. Neutral faces were morphed with angry or happy faces in 25% intervals. In specific phases of the task, youth alternatively made explicit (hostility) or implicit (nose width) ratings of the faces. The slope of blood oxygenated level‐dependent activity was calculated across neutral to angry and neutral to happy face stimuli. Results Behaviorally, both subjects with BD (p ≤ 0.001) and AR youth (p ≤ 0.05) rated faces as less hostile relative to HC. Consistent with this, in response to increasing anger on the face, patients with BD and AR youth showed decreased modulation in the amygdala and inferior frontal gyrus (IFG; BA 46) compared to HC (all p ≤ 0.05). Amygdala dysfunction was present across both implicit and explicit rating conditions, but IFG modulation deficits were specific to the explicit condition. With increasing happiness, AR youth showed aberrant modulation in the IFG, which was also sensitive to task demands (all p ≤ 0.05). Conclusions Decreased amygdala and IFG modulation in patients with BD and AR youth may be pathophysiological risk markers for BD, and may underlie the social cognition and face emotion labeling deficits observed in BD and AR youth.